2017
DOI: 10.1021/acs.jmedchem.6b01609
|View full text |Cite
|
Sign up to set email alerts
|

Development of 1,2,4-Oxadiazoles as Potent and Selective Inhibitors of the Human Deacetylase Sirtuin 2: Structure–Activity Relationship, X-ray Crystal Structure, and Anticancer Activity

Abstract: Sirt2 is a target for the treatment of neurological, metabolic, and age-related diseases including cancer. Here we report a series of Sirt2 inhibitors based on the 1,2,4-oxadiazole scaffold. These compounds are potent Sirt2 inhibitors active at single-digit μM level by using the Sirt2 substrate α-tubulin-acetylLys40 peptide and inactive up to 100 μM against Sirt1, -3, and -5 (deacetylase and desuccinylase activities). Their mechanism of inhibition is uncompetitive toward both the peptide substrate and NAD, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(70 citation statements)
references
References 68 publications
2
67
0
1
Order By: Relevance
“…Thus SIRT2 may provide an additional link between K-Ras4a signaling and cellular metabolism. Given that Ras proteins play critical roles in many human cancers, SIRT2, as a Ras regulator, may be an important therapeutic target for cancer, which is consistent with several recent reports ( Jing et al, 2016 ; Moniot et al, 2017 ; Shah et al, 2016 ; Wang et al, 2014 ; Wilking-Busch et al, 2017 ; Xu et al, 2016 ; Zhao et al, 2013 , 2016 ). The physiological and pathophysiological roles of SIRT2 thus merit further investigation.…”
Section: Discussionsupporting
confidence: 89%
“…Thus SIRT2 may provide an additional link between K-Ras4a signaling and cellular metabolism. Given that Ras proteins play critical roles in many human cancers, SIRT2, as a Ras regulator, may be an important therapeutic target for cancer, which is consistent with several recent reports ( Jing et al, 2016 ; Moniot et al, 2017 ; Shah et al, 2016 ; Wang et al, 2014 ; Wilking-Busch et al, 2017 ; Xu et al, 2016 ; Zhao et al, 2013 , 2016 ). The physiological and pathophysiological roles of SIRT2 thus merit further investigation.…”
Section: Discussionsupporting
confidence: 89%
“…Thus SIRT2 may provide an additional link between K-Ras4a signaling and cellular metabolism. Given that Ras proteins play critical roles in many human cancers, SIRT2, as a Ras regulator, may be an important therapeutic target for cancer, which is consistent with several recent reports 50,53, 54,57,58,8587 . The physiological and pathophysiological roles of SIRT2 thus merit further investigation.…”
Section: Discussionsupporting
confidence: 88%
“…In the crystal structures of sirt1, it was shown that substrates make H-bond interactions with the backbone of a conserved valine residue (sirt1 numbering Val412) which is crucial for the correct orientation of the acyl-lysine in the active site [44]. In case of sirt2, we first examined the binding interactions of the native ligands including both the peptide substrates, the cofactor fragments and the co-crystallized inhibitors with the protein [31][32][33][34][35][36][37][38][39][40][41][42][43]. In the hit selection process, a special importance was given to compounds that were able to interact with residues Phe234, Phe235, Phe190 and Glu237 in the catalytic pocket.…”
Section: Docking Scoring and Hit Selectionmentioning
confidence: 99%
“…Within the last two decades, several sirt1 and sirt2 crystal structures have been solved in both apo and holo forms [31][32][33][34][35][36][37][38][39][40][41][42][43]. Ternary structures of sirt1 and sirt2 in complex with cofactor analogues, peptide-based and structurally diverse inhibitors revealed a high conformational flexibility in the catalytic pocket, especially in the extended C-pocket region.…”
Section: Introductionmentioning
confidence: 99%